New communication practices on the radio and in the audiosphere - Bachura-Wojtasik, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
For the past decade or so, internet radio, podcasts, mobile sound apps, and digital libraries of audio content have enjoyed increasing popularity among researchers and receivers of culture. Radio, similarly to other traditional media, often experiments with the opportunities offered by the new media technologies enabling the emergence of new communicational practices. As a starting point, I consider the contemporary audiosphere, which constitutes the auditory part of the audio-visual culture, and the influence of technological changes on radio communications, artists, and receivers. I attempt to answer the question, what happens at genre fringes? What are the characteristic features of the emerging forms? How, when one is faced with new technology, the multimedia world, and virtual reality, can one reach a reflection on the fiction and non-fiction genres on the radio? The expansive character of new technologies is often the source of inspiration for that which is traditional, thus renewing the object of its study. The inclusion of new phenomena within the widely understood auditoriness has a rescuing nature for traditional forms, and, at the same time, offers new opportunities for creators, and thus an area of research for literary scientists, media scientists and literary critics.